Mie scattering from optically levitated mixed sulfuric acid–silica core–shell aerosols: observation of core–shell morphology for atmospheric science. Issue 10 (28th February 2022) - McGrory, Megan R.; Shepherd, Rosalie H.; King, Martin D.; Davidson, Nicholas; Pope, Francis D.; Watson, I. Matthew; Grainger, Roy G.; Jones, Anthony C.; Ward, Andrew D.
Abstract : Sulfuric acid is shown to form a core–shell particle on a micron-sized, optically-trapped spherical silica bead. Abstract : Sulfuric acid is shown to form a core–shell particle on a micron-sized, optically-trapped spherical silica bead. The refractive indices of the silica and sulfuric acid, along with the shell thickness and bead radius were determined by reproducing Mie scattered optical white light as a function of wavelength in Mie spectroscopy. Micron-sized silica aerosols (silica beads were used as a proxy for atmospheric silica minerals) were levitated in a mist of sulfuric acid particles; continuous collection of Mie spectra throughout the collision of sulfuric acid aerosols with the optically trapped silica aerosol demonstrated that the resulting aerosol particle had a core–shell morphology. Contrastingly, the collision of aqueous sulfuric acid aerosols with optically trapped polystyrene aerosol resulted in a partially coated system. The light scattering from the optically levitated aerosols was successfully modelled to determine the diameter of the core aerosol (±0.003 μm), the shell thickness (±0.0003 μm) and the refractive index (±0.007). The experiment demonstrated that the presence of a thin film rapidly changed the light scattering of the original aerosol. When a 1.964 μm diameter silica aerosol was covered with a film of sulfuric acid 0.287 μm thick, the wavelength dependent Mie peak positions resembled sulfuric acid. Thus mineral aerosol advected into the stratosphere would likely be coated with sulfuric acid, with a core–shell morphology, and its light scattering properties would be effectively indistinguishable from a homogenous sulfuric acid aerosol if the film thickness was greater than a few 100 s of nm for UV-visible wavelengths.